SYNTHESIS OF 3-ARYLISOCOUMARINES WITH SULFAMIDE GROUPS: UDC 547.814.5 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Interaction of 3-arylisocoumarines and Chlorosulfonic acid was investigated. Method of creation of pharmacophore sulfamide fragment into the 3-arylisocoumarine molecule was proposed.
Keywords: isocoumarins (1H-isochromen-1-ones), chlorosulfonation, sulfonamides